Analisis Kompetensi Dasar Buku Tematik Kelas IV Tema 9 Makanan Sehat dan Bergizi - Abroto; Febriyani Awliyah, Rizka (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2022)
Curriculum changes certainly affect many aspects of education, one of which is learning resources in the form of textbooks. Textbooks that originally contained one subject are now packaged into thematic book that integrate several subjects into one theme. The purpose of this study is to explain the suitability of thematic studies 4th grade Theme 1 Beautiful Diversity in PPKn subjects with basic competencies of the 2013 curriculum. Also explain the suitability of thematic integrated book lesson grade IV theme 1, Beautiful Diversity in the basic competence of PPKn curiculum 2013. The research method used in this study is a literature study method with a qualitative approach. The results of the study showed that the basic competencies used in class IV text book theme 1 Beautiful Diversity was in accordance with the PPKn subject in the 2013 basic competencies. However, there are differences in mapping basic competencies in sub-themes 1, 2, and 3. Mapping the basic competencies in 1st subtheme there are four basic competencies. While the basic competency mapping in sub-themes 2nd and 3rd there are six basic competencies. There are two basic competencies for spiritual and social core competencies